Analysis of surgical outcome and review of literature of schwannomas arising from the extremities - Wahegaonkar, Chandrashekhar; Patil, Bhushan; Sharma, Alok; Dogra, Bharat Bhushan (International Journal of Research in Medical Sciences, 2019)
Background: Schwannoma is a benign peripheral nerve sheath tumour derived from Schwann cells. Also known as Neurilemoma, it can affect any nerve in the body. They usually present as a painless swelling or paresthesia over the sensory distribution of the affected nerve. Although it is classically described that schwannomas are well encapsulated and can be completely enucleated during excision, many of them have fascicular involvement and could not be completely shelled out. The aim of this work is to present our experience in operative management of schwannomas located in extremities. Methods: Authors conducted a retrospective review for 18 adult patients with schwannoma, from June 2012 to June 2018. There were 10 men and 8 women, ranging from 20 to 68 years of age, with a mean age of 46 years old. All patients had excision done for the tumour and histopathological examination confirmed schwannoma. All patients were preoperatively evaluated both clinically and radiologically. FNAC was also done to confirm the origin of the swelling. Results: The mean follow up period has been 2 years. Complete excision with preservation of nerve was done in all cases except for one case in which nerve graft was used. Conclusions: Use of preoperative MRI, magnification and good surgical technique will help to enucleate the tumour completely without any collateral damage or recurrence. The possibility and option of nerve graft should be discussed with patients prior to schwannoma excision, so that nerve grafting could be directly proceeded with patient consent in case there is fascicular involvement of tumour found intraoperatively.